2022
DOI: 10.3389/froh.2022.974644
|View full text |Cite
|
Sign up to set email alerts
|

Can aerosols-generating dental, oral and maxillofacial, and orthopedic surgical procedures lead to disease transmission? An implication on the current COVID-19 pandemic

Abstract: Various dental, maxillofacial, and orthopedic surgical procedures (DMOSP) have been known to produce bioaerosols, that can lead to the transmission of various infectious diseases. Hence, a systematic review (SR) aimed at generating evidence of aerosols generating DMOSP that can result in the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), further investigating their infectivity and assessing the role of enhanced personal protective equipment (PPE) an essential to preventing the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 120 publications
(154 reference statements)
0
1
0
Order By: Relevance
“…Improper handling of MARV-infected corpses poses a significant risk as it may result in irresponsible transmission of virus. Furthermore, certain studies have suggested the potential for fomites or aerosol-borne transmission of virus (Leffel and Reed 2004;Dobler et al 2012;Al-Moraissi et al 2022).…”
Section: Transmission Routesmentioning
confidence: 99%
“…Improper handling of MARV-infected corpses poses a significant risk as it may result in irresponsible transmission of virus. Furthermore, certain studies have suggested the potential for fomites or aerosol-borne transmission of virus (Leffel and Reed 2004;Dobler et al 2012;Al-Moraissi et al 2022).…”
Section: Transmission Routesmentioning
confidence: 99%